2017
DOI: 10.1002/hed.24748
|View full text |Cite
|
Sign up to set email alerts
|

Cohort study of oncologic emergencies in patients with head and neck cancer

Abstract: Background Treatments for squamous cell carcinoma of the head and neck (HNSCC) are associated with toxicities that lead to emergency department (ED) presentation. Methods We utilized data from an ongoing prospective cohort of newly diagnosed, previously untreated patients (N=298) with HNSCC to evaluate the association between clinical and epidemiologic factors and risk and frequency of ED presentation. Time to event was calculated from the date of treatment initiation to ED presentation, date of death, or cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Fungal and virus infections in the oral cavity are common in immunocompromised patients [10,25,26]. Similarly, our results showed a prevalence of 5.6 and 5.1% for oral candidiasis and oral herpes simplex, respectively; while in previously published retrospective studies evaluating oncologic inpatients, the incidences ranged from 16.6 to 39.1% [3,[9][10][11].…”
Section: Discussionsupporting
confidence: 85%
“…Fungal and virus infections in the oral cavity are common in immunocompromised patients [10,25,26]. Similarly, our results showed a prevalence of 5.6 and 5.1% for oral candidiasis and oral herpes simplex, respectively; while in previously published retrospective studies evaluating oncologic inpatients, the incidences ranged from 16.6 to 39.1% [3,[9][10][11].…”
Section: Discussionsupporting
confidence: 85%
“…The visits to ED have been found to be associated with the presence of comorbidities, advanced stage of the disease, and chemoradiation. [57] Another study found chemotherapy to be associated with unplanned admissions. [8] This could be because of decreased blood counts and higher risks for infections.…”
Section: Discussionmentioning
confidence: 99%
“…OM interferes with oral intake and can lead to a reduction in the treatment dose, unplanned hospitalizations (which increase the cost of care), breaks in the treatment regimen, 1,4,5 a reduced quality of life, and an impact on overall survival. Subsequent emergency department visits for OM‐related complaints are common, and they persist as a chief complaint for 15% to 23% of patients across emergency department visits 6 . Standard treatment for OM focuses on pain control, rehydration, and oral hygiene.…”
Section: Introductionmentioning
confidence: 99%